Neonatal herpes simplex virus infections: HSV DNA in cerebrospinal fluid and serum. Issue 1 (1st July 1999) - Malm, G; Forsgren, M
Abstract : AIM: To investigate the diagnostic potential of herpes simplex virus (HSV) DNA in cerebrospinal fluid and serum; to correlate the findings with outcome in the child and with type of maternal infection. METHODS: Cerebrospinal fluid and serum specimens from 36 children with verified neonatal HSV infections, diagnosed between 1973 and 1996, were examined using the polymerase chain reaction technique (PCR). RESULTS: In 21 children for whom both cerebrospinal fluid and sera were available, HSV DNA was found in one or both specimens in 19 (90%). Overall, HSV DNA was found in the cerebrospinal fluid of 74% of 27 children, and in the sera of 20 out of 30 children (67%). In two children HSV DNA was not demonstrable in either serum or cerebrospinal fluid. In sequential specimens from four children, the persistence of HSV DNA after the end of intravenous treatment was associated with a poor prognosis. CONCLUSIONS: These findings indicate that HSV DNA detection in CSF and serum is highly sensitive for the diagnosis of neonatal HSV infections but does not replace the detection of virus in other locations using virus isolation and antigen detection.